SUPERAÇÃO DA TESE DO MERO ABORRECIMENTO ENQUANTO OBJETO DE MANUTEÇÃO DO PRECONCEITO À POPULAÇÃO LGBTQIAP+ - ADOLFO ALDERETE FILHO (2024)
Due to the negligence of the State, homophobia has been applied in different ways in Brazil, because although there is a legal system that criminalizes it, it appears in different areas, even if in a veiled way. As for moral damage, it is often disregarded because they associate homophobia with mere annoyance, ensuring that the fight against prejudice in the legal field is still in a very abstract space. The methodology applied was bibliographic and documentary, through deducibility. Finally, understanding that the only possibility of a solution to the problem presented would be legislative changes regarding the fight against prejudice, but above all mechanisms that guarantee its real and effective application, especially regarding the impossibility of using the theory of mere annoyance to mischaracterize real damages moral suffering suffered by the victims.